UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI AKHLAK DI SEKOLAH DASAR ISLAM TERPADU - Fauzieah Lathiifah Nurfahmi; Nur Hidayah; Herri Gunawan (Al'Ulum Jurnal Pendidikan Islam, 2022)
The negative impact of scientific and technological development, the lack of understanding about promiscuity, and the shifting moral values resulted the importance of instilling moral values in students from an early age. The purpose of this research is to describe and explain the efforts of Islamic Religious Education teachers in instilling moral values and also the inhibiting factor in the effort to instill moral values at SDIT Luqman Al Hakim Surakarta. This research is qualitative research with a descriptive qualitative research design. The subject of this study is Islamic Religious Education teachers in female fifth grade, while the informants are the principal and education staff of SDIT Luqman Al Hakim Surakarta. The data collection is through observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation, and also conclusion. Based on the results of the research, the efforts of Islamic Religious Education teachers in instilling moral values by introducing tauhid, giving advice, habituation of having moral values, being a pleasant figure, and providing good examples The inhibiting factor in instilling moral values is due to the limited supervision of the teachers. In addition, there are other factors outside the authority of the school that must be considered, namely the family environment, the use of social media and the community environment.